2013
DOI: 10.1111/cen.12282
|View full text |Cite
|
Sign up to set email alerts
|

Thyroglobulin as early prognostic marker to predict remission at 18–24 months in differentiated thyroid carcinoma

Abstract: Baseline-stimulated Tg is a good predictor of remission of disease at 18-24 months after initial treatment and could be a useful marker to stratify risk immediately after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…Previous studies have focused on sTg only as a laboratory parameter for predicting the ablation outcome [16, 27]. A recent retrospective study conducted on 133 patients revealed that a preablation sTg < 8.55 ug/L predicted disease remission after 18–24 months of RRA with sensitivity of 88%, specificity of 72%, positive predictive value (PPV) of 47%, and negative predictive value (NPV) of 95% [18]. Another study conducted on 96 patients in Brazil found that patients with sTg levels < 18 ng/mL before RRA had 5.89 times greater chance of successful ablation compared to those with sTg > 18 ng/mL ( P < 0.0001) with sensitivity of 71.4%, specificity of 70.2%, PPV of 71.4%, and NPV of 70.2% [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have focused on sTg only as a laboratory parameter for predicting the ablation outcome [16, 27]. A recent retrospective study conducted on 133 patients revealed that a preablation sTg < 8.55 ug/L predicted disease remission after 18–24 months of RRA with sensitivity of 88%, specificity of 72%, positive predictive value (PPV) of 47%, and negative predictive value (NPV) of 95% [18]. Another study conducted on 96 patients in Brazil found that patients with sTg levels < 18 ng/mL before RRA had 5.89 times greater chance of successful ablation compared to those with sTg > 18 ng/mL ( P < 0.0001) with sensitivity of 71.4%, specificity of 70.2%, PPV of 71.4%, and NPV of 70.2% [16].…”
Section: Discussionmentioning
confidence: 99%
“…However limitation of our study was its retrospective nature; therefore, we could retrieve data of only 75 patients who fulfilled our inclusion criteria. Many of the previous studies regarding role of sTg in predicting RRA outcome were also retrospective in nature [8, 15, 16, 18, 29, 31]. Another limitation of this study is use of different ablative doses in low, intermediate, and high risk groups which could have an impact on success of ablation as British Thyroid Association 2007 guidelines favor use of high dose for RRA [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, pre-ablation stimulated Tg is known to be a good predictor of successful ablation in DTC patients 14 . Pre-ablation Tg has also been demonstrated as an important indicator for predicting persistence or recurrence during follow-up 15 16 17 . However, cut-off values of Tg for successful ablation or recurrence prediction were quite different among the above mentioned studies.…”
mentioning
confidence: 99%
“…Analysis of the ROC showed that when 7.25 mm was used as the cut-off diameter of the lymph nodes for the prediction of poor prognosis, the Youden index was the highest (0.759), and the corresponding sensitivity and specificity were 93.3% and 82. [8][9][10]. Lee et al [11] have used 2 ng/ml as the cut-off ps-Tg level to predict the disease-free survival of DTC patients, and the NPV was as high as 94.9%.…”
Section: Association Between Lymph Node Sizes and Clinical Outcomesmentioning
confidence: 99%